Significados Atribuidos a Las Relaciones Parentales de un Grupo De Padres y Madres de Adolescentes Sancionados Por Comisión de Delitos Asociados al Consumo de Sustancias Psicoactivas (Spa) (2016)
The present research was conducted in order to acquire knowledge about the dominant narratives of adolescents´ parents punished for committing crimes associated with the use of psychoactive substances, based on interviews with two mothers and one father who were charged with 4-hour per day extra work at the Pastoral Office Family and Children Care (Bogotá) in mode System of Criminal Responsibility. For this, a qualitative methodology, thus describing the lifestyle of the families involved in the research, knowing their relations roles, rules are designed, standards and communication style from a systemic theoretical approach. The techniques used to gather information were conducting through open each participant interview.